Sleep problems in children with autism spectrum disorder in Hong Kong: a cross-sectional study - Leung, Man Ho Brian; Ngan, Sze Ting Joanna; Cheng, Pak Wing Calvin; Chan, Fong Chun Grace; Chang, Wing Chung; Cheung, Hoi Kei; Ho, Chung; Lee, Chi Kei Krystal; Tang, Yiu Chung Vincent; Wong, Siu Man Corine; Chan, Kwok Ling Phyllis (Frontiers in Psychiatry, 2023)
Background Autism spectrum disorder (ASD) is a neurodevelopmental disorder with a growing prevalence of sleep problems associated with significant behavioral problems and more severe autism clinical presentation. Little is known about the relationships between autism traits and sleep problems in Hong Kong. Therefore, this study aimed to examine whether children with autism have increased sleep problems than non-autistic children in Hong Kong. The secondary objective was to examine the factors associated with sleep problems in an autism clinical sample. Methods This cross-sectional study recruited 135 children with autism and 102 with the same age range of non-autistic children, aged between 6 and 12 years. Both groups were screened and compared on their sleep behaviors using the Children's Sleep Habits Questionnaire (CSHQ). Results Children with autism had significantly more sleep problems than non-autistic children [t(226.73) = 6.20, p < 0.001]. Bed -sharing [beta = 0.25, t(165) = 2.75, p = 0.07] and maternal age at birth [beta = 0.15, t(165) = 2.05, p = 0.043] were significant factors associated with CSHQ score on the top of autism traits. Stepwise linear regression modeling identified that only separation anxiety disorder (beta = 4.83, t = 2.40, p = 0.019) best-predicted CSHQ. Conclusion In summary, autistic children suffered from significantly more sleep problems and co-occurring separation anxiety disorder brings greater sleep problems as compared to non-autistic children. Clinicians should be more aware of sleep problems to provide more effective treatments to children with autism.